دوراليقظةاالستراتيجيةفي تفعيل إدارةالعرفة دراسةميدانيةبمؤسسة اتصاالت الجزائر وكالةالوادي - مصباح مصباحي; رويده لبزة (university of eloued جامعة الوادي, 2025)
اصبح مستقبل العالم يعتمد على من يستغل الفرص اولا , ويتجنب التهديدات المحيطة به , قبل الاخرين , وفي قطاع الاقتصادي و الاداري غير بعيد على هذه الامور , فأصبحت المعلومة ومن يمتلكها هو صاحب الفرصة الاكبر لنجاح مقارنة بغيره , فاتجهت الشركات العالمية للاستثمار في طرق و اساليب البحث على المعلومة , و الوسيلة الافضل لذلك هي اليقظة الاستراتيجية و التي تعمل على رصد كل متغيرات البيئة الخارجية لشركات ,والتي تمكن المؤسسة من تحديث و زيادة مخزونها من المعلومة حول عالمها الخارجي , والتي توفر لها امكانية استغلال الفرص , وتجنب التهديدات التي قد تصادفها, و تمكن المؤسسة من ادارة المعرفة الخاصة بها , ولذلك جاءت هذه الدراسة لمعرفة دور اليقظة الاستراتيجية في تفعيل ادارة المعرفة , وأخذنا اتصالات الجزائر وكالة الوادي كحالة دراسة , معتمدين على توزيع استمارات على العمال من اجل جمع البيانات , واستعملت اساليب احصائية من اجل تحليل تلك البيانات , مثل المتوسط الحسابي , الانحراف المعياري , معامل الفا كرو نباخ , و نتج على هذه الدراسة مجموعة من التوصيات نذكر منها : ضرورة اعتماد المؤسسات الحكومية على نظام اليقظة الاستراتيجية بها, ضرورة تركيز على انواع اليقظة الاستراتيجية , و دالك من اجل الوصول الى نظام ادارة المعرفة محدث و مطور من حيث المعلومات التي يحوزها . The future of the world has become dependent on those who exploit opportunities first, and avoid threats surrounding it, before others, and in the economic and administrative sector is not far from these matters, so the information and those who possess it became the owner of the greatest opportunity for success compared to others, so international companies tended to invest in methods and methods of research on information, and the best way for this is strategic vigilance, which works to monitor all the variables of the external environment for companies, which enables the organization to update and increase its stock of information about its external world, which provides it with the possibility of exploiting opportunities, avoiding threats that may occur, and enabling the organization to manage its knowledge, Therefore, this study came to find out the role of strategic vigilance in activating knowledge management, and we took Algeria Telecom as a case study, relying on the distribution of questionnaires to workers in order to collect data, and statistical methods were used to analyze those data, such as arithmetic mean, standard deviation, alpha coefficient, and Cronbach's alpha, and this study resulted in a set of recommendations, including the following: The need for governmental organizations to adopt a strategic vigilance system, the need to focus on the types of strategic vigilance, in order to reach an updated and developed knowledge management system in terms of the information it holds.
ماستر علوم اقتصادية
Keywords: اليقظة،; اليقظة الاستراتيجية،; اليقظة التنافسية; المعرفة; ادارة المعرفة; Vigilance; strategic vigilance. technological vigilance; competitiveness Vigilant; Knowledge. Knowledge management.